Salty fertile lakes: how salinization and eutrophication alter the structure of freshwater communities. Issue 9 (17th September 2018) - Lind, Lovisa; Schuler, Matthew S.; Hintz, William D.; Stoler, Aaron B.; Jones, Devin K.; Mattes, Brian M.; Relyea, Rick A.
Abstract: The quality of freshwater ecosystems is decreasing worldwide because of anthropogenic activities. For example, nutrient over‐enrichment associated with agricultural, urban, and industrial development has led to an acceleration of primary production, or eutrophication. Additionally, in northern areas, deicing salts that are an evolutionary novel stressor to freshwater ecosystems have caused chloride levels of many freshwaters to exceed thresholds established for environmental protection. Even if excess nutrients and road deicing salts often contaminate freshwaters at the same time, the combined effects of eutrophication and salinization on freshwater communities are unknown. Thus by using outdoor mesocosms, we investigated the potentially interactive effects of nutrient additions and road salt (NaCl) on experimental lake communities containing phytoplankton, periphyton, filamentous algae, zooplankton, two snail species ( Physa acuta and Viviparus georgianus ), and macrophytes ( Nitella spp.). We exposed communities to a factorial combination of environmentally relevant concentrations of road salt (15, 250, and 1000 mg Cl − /L), nutrient additions (oligotrophic, eutrophic), and sunlight (low, medium, and high) for 80 d. We manipulated light intensity to parse out the direct effects of road salts or nutrients from the indirect effects via algal blooms that reduce light levels. We observed numerous direct and indirect effects of salt, nutrients, and light as well as interactive effects. Added nutrients caused increases in most producers and consumers. Increased salt (1000 mg Cl − /L) initially caused a decline in cladoceran and copepod abundance, leading to an increase in phytoplankton. Increased salt also reduced the biomass and chl a content of Nitella and reduced the abundance of filamentous algae. Added salt had no effect on the abundance of pond snails, but it caused a decline in banded mystery snails, which led to an increase in periphyton. Low light negatively affected all taxa (except Nitella ) and light levels exhibited multiple interactions with road salt, but the combined effects of nutrients and salt were always additive. Collectively, our results indicate that eutrophication and salinization both have major effects on aquatic ecosystems and their combined effects (through different mechanisms) are expected to promote large blooms of phytoplankton and periphyton while causing declines in many species of invertebrates and macrophytes.